Stability analysis on yield of several winged bean lines (Psophocarpus tetragonolobus L.) in three environments - Dian Rakhmad; Muhamad Syukur (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Winged bean is a plant with a high seed protein content equivalent to soybeans. Indonesia is one of the central origins in southern Asia. However, there are still only a few superior varieties that can be widely cultivated. One effort to increase productivity is by growing improved varieties. This study aimed to identify promising winged bean lines with high and stable yield potential. The experiment was conducted in three environments, i.e., two planting seasons in Bogor and one in Palembang from January 2019 to June 2020. A total of 11 winged bean genotypes were tested and observed for grain yield characters. Parametric analysis methods were used to obtain information on the stability of 11 winged bean genotypes across the three environments. Grain yield was significantly affected by G x E interaction and, therefore, was subjected to stability analyses. Genotypes H1(P), L2, and H4(P) were classified as stable. This genotype had similar characteristics with stable grain yield in three test environments. Keywords: G x E interaction; seed yield; parametric stability, underutilized legume